1996
DOI: 10.1002/(sici)1099-1565(199611)7:6<279::aid-pca322>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids of Cannabis Seeds

Abstract: The chemical composition of the fatty acids in twenty four different samples of cannabis seeds was determined by gas liquid chromatography with flame ionization detector and coupled with a mass spectrometer. The identification of twenty fatty acids was based on comparison with authentic samples. In addition six other components were detected in some samples and shown to be oxygenated acids. The data showed that the seeds could be divided broadly into two groups, one with saturated and unsaturated fatty acids a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 4 publications
3
20
0
1
Order By: Relevance
“…α-Linolenic acid (ALA) content in the oil is about 15-34%. The highest GLA and SDA concentrations were found in seeds grown in extreme northern climatic regions and seeds of drug varieties of Cannabis sativa L. grown in tropical regions, Mexico, Thailand, Colombia, and Jamaica, did not contain ALA (Ross et al, 1996). Although the ideal ω-6:ω-3 ratio for optimal health is recognized as 3:1-5:1, the topic is still controversial (Kinsella et al, 1990; Layne et al, 1996).…”
Section: Hemp Seed Oil Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…α-Linolenic acid (ALA) content in the oil is about 15-34%. The highest GLA and SDA concentrations were found in seeds grown in extreme northern climatic regions and seeds of drug varieties of Cannabis sativa L. grown in tropical regions, Mexico, Thailand, Colombia, and Jamaica, did not contain ALA (Ross et al, 1996). Although the ideal ω-6:ω-3 ratio for optimal health is recognized as 3:1-5:1, the topic is still controversial (Kinsella et al, 1990; Layne et al, 1996).…”
Section: Hemp Seed Oil Compositionmentioning
confidence: 99%
“…The health benefits of hemp seed oil is attributed to its desirable ω-6:ω-3 fatty acid ratio, 3:1. Ross et al (1996) reported that the saturated fatty acid content of the seeds decreased as the seeds matured. The National Academy of Sciences (2002) recommends a ω-6:ω-3 ratio of 5:1-10:1 for adults.…”
Section: Hemp Seed Oil Compositionmentioning
confidence: 99%
“…Regarding the yield of hemp seed oil, values between 35.27% and 36.88% were recorded in the northwest of Turkey [23]. The quantitative difference in the content of hemp oils could be explained by the effects of environmental factors and the storage methods [20,24,25].…”
Section: Discussionmentioning
confidence: 53%
“…Seed maturity also effects the fatty acids composition: the more mature the seeds the higher is the percentage of unsaturated fatty acids and the lower the percentage of saturated ones (Ross et al, 1996). Accordingly, sampled hempseed oil characteristics did not present critically different values vis-à-vis non-Sicilian hemp oil composition.…”
Section: Understanding the Nutraceutical And Taste Levermentioning
confidence: 89%